A low band-gap copolymer composed of thienyl substituted anthracene and diketopyrrolopyrrole compatible with multiple electron acceptors for high efficiency polymer solar cells1. Issue 21 (7th June 2015) - Jung, Jae Woong; Jo, Won Ho
<x xml:space="preserve">Abstract</x> A low band-gap polymer composed of thienylanthracene and DPP exhibits promising PCEs of 7.02% with PC71BM, and 4.23% with non-fullerene acceptor di-PBI, demonstrating the potential for universal electron donor polymer of polymer solar cells.